Mewaspadai Secondary Traumatic Stress Saat Memberi Pelayanan Konseling - Amirah Diniaty (Indonesian Institute for Counseling, Education and Therapy (IICET), 2014)
Not infrequently counselor faced with complicated problems and traumatic outstanding experienced by the client. According to Figley and Stamm (in Stamm, 1999), a trauma counselor can come to experience some of the symptoms are similar to Post Traumatic Stress Disorder (PTSD), which is owned by their clients. Figley (in Richardson, 2001) defines this situation with Secondary Traumatic Stress (hereinafter referred to as STS), which is something that occurs naturally, is a behavioral and emotional consequences as a result of knowledge about a traumatic event experienced by a significant other. The term 'secondary' refers to the fact that the trauma experienced by others, but then experienced by the participating parties observe, giving aid, or listen to the story (Sidabutar, 2003). This is the